2015
DOI: 10.3923/rjes.2015.169.177
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Iron Using Rhamnolipid-Surfactant Produced by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa was isolated from 20 years abandoned mine site of Itagunmodi Atakunmosa West, Ilesha, Nigeria. Atomic absorption Spectrophotometry (AAS) revealed Fe, Mn, Cr, Zn, Pb and Cr, while, Fe has the highest concentration range of 29-289 ppm in the analysed soil samples. Soil samples were enriched in R2b agar, serially diluted and pour plated. Four bacteria strains were isolated and identified using standard biochemical test. After routine biosurfactant screening by oil spreading and emulsificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These decreases in Pb content in the PL fraction are due to removal of Pb from iron oxides and the results suggest that RAM more effectively releases Pb from these oxides than plant biosurfactants. Akintunde et al (2015) confirmed that the Fe concentration in soil was decreased about 60% by RAM. Neilson et al (2003) found that, although RAM did not effectively remove Pb from heavily contaminated (3780-23,900 mg/kg) aged soils, they were more effective than carboxymethyl-beta-cyclodextrin for removing Pb bound to amorphous iron oxides.…”
Section: The Effect Of Single Washing With Biosurfactants On Hm Distrsupporting
confidence: 53%
“…These decreases in Pb content in the PL fraction are due to removal of Pb from iron oxides and the results suggest that RAM more effectively releases Pb from these oxides than plant biosurfactants. Akintunde et al (2015) confirmed that the Fe concentration in soil was decreased about 60% by RAM. Neilson et al (2003) found that, although RAM did not effectively remove Pb from heavily contaminated (3780-23,900 mg/kg) aged soils, they were more effective than carboxymethyl-beta-cyclodextrin for removing Pb bound to amorphous iron oxides.…”
Section: The Effect Of Single Washing With Biosurfactants On Hm Distrsupporting
confidence: 53%
“…This coordinate regulation may aid in iron acquisition as QS-controlled phenazines, such as pyocyanin, reduce poorly soluble Fe 3ϩ to Fe 2ϩ and facilitate its uptake via the Feo system (92). Additionally, rhamnolipids have been employed for iron remediation (93,94), which suggests that their surfactant activity may increase P. aeruginosa substrate iron uptake in part through hydroxy-alkylquinolone-dependent mechanisms (95).…”
Section: Discussionmentioning
confidence: 99%
“… 107 Rhamnolipid-sa1 alone was reported to be effective to reduce iron up to 60.34% from the contaminated soil. 108 Another plant extracted biosurfactant, saponin, was believed to be efficient for removing heavy metals (Cu, Zn, Cr, Pb, Ni, Mn) using a sequential sludge washing method through the proposed mechanism in Fig. 7 .…”
Section: Biosurfactant Assisted Bioremediation Of Soilmentioning
confidence: 99%